Instant Formulation of Inhalable Beclomethasone Dipropionate-Gamma-Cyclodextrin Composite Particles Produced Using Supercritical Assisted Atomization - Hsien-Tsung Wu; Han-Cyuan Lin; Yi-Jia Tu; Kim Hoong Ng (MDPI AG, 2023)
Medical composites derived from Gamma-cyclodextrin (γ-CD) and beclomethasone dipropionate−gamma-cyclodextrin (BDP−γ-CD) are synthesized over supercritical-assisted atomization (SAA) herein. Carbon dioxide, which serves the dual function of spraying medium and co-solute, is incorporated in this process along with the ethanolic solvent. Results indicate that, for fine spherical particles, optimized aerosol performance could be obtained with 50.0% (w/w) ethanolic solvent, precipitator, and saturator at 373.2 K and 353.2 K, respectively, and carbon dioxide-to-γ-CD flow ratio of 1.8 in the presence of 10 wt% leucine (LEU) as dispersion enhancer. It is also noted that γ-CD solution at low concentration typically renders better aerosol performance of the particles. During drug particle-derivation, the solubility of drug BDP elevated considerably due to the formation of inclusion complexes, further assisted by the ethanolic solvent which increases the lipophilicity of BDP. Meanwhile, the in vitro aerosolization and dissolution performance of drug composites derived from varied γ-CD-to-BDP mass ratio (Z) were also evaluated. It was found that high Z promises higher fine particle fraction in the obtained drug composite while the dissolution rate of active ingredient (BDP) exhibits positive correlation to the content of water-soluble excipient (γ-CD) in the formulation. This study offers a new avenue for instant drug formulation with promising pulmonary delivery over the SAA technique.